A retrospective single center analysis of fetuses with region of homozygosity detected by single nucleotide polymorphism array - Xiufen Bu; Xiuyun Yu; Li Zeng; Guo Zeng; Rong Tan; Can Peng; Shihao Zhou; Siyuan Linpeng; Jing Liu (Scientific Reports)
Abstract We assessed the incidence and clinical significance of the fetal region of homozygosity (ROH) detected using single nucleotide polymorphism (SNP) array by analyzing clinical information and pregnancy outcomes. We collected data on 6176 mid- and late pregnancies. All fetuses were subjected to SNP array analysis. Fetuses with ROH were analyzed by karyotyping, parental SNP array verification, whole-exome sequencing, and/or placental studies. Eighty-seven ROHs met our reporting thresholds. Thirty-four fetuses were detected from noninvasive prenatal testing-positive results, with the most common detection rate (2.03%). Twenty-four cases were diagnosed using ultrasound abnormalities; fetal growth restriction was the indication with the highest diagnostic rate. Fifteen cases of uniparental disomy in mid- and late pregnancy were identified (0.24%). Nine cases were of ROH accompanied by aneuploidy or pathogenic/likely pathogenic copy number variants with an adverse pregnancy outcome rate of 88.9%. Of the remaining 78 cases, 14 carriers had adverse outcomes (including two cases of imprinting syndrome), 63 had normal development after birth, and one was lost to follow-up. ROH is relatively common in mid- and late-term pregnancies; its incidence is higher than that reported previously. SNP array is effective in assessing ROH and should be combined with multiple techniques to evaluate ROH’s clinical relevance.